2022
DOI: 10.1002/jmv.27810
|View full text |Cite
|
Sign up to set email alerts
|

Vaccines for Covid‐19: An insight on their effectiveness and adverse effects

Abstract: An era of SARS‐COVID‐19 outbreak with a high contagious percentage around the globe has been the subject of multi‐agency research aimed at generating vaccines for active immunization. Scientists across the world are joining hands for advanced tie‐ups between medical start‐ups and pharmaceutical industries for devices and vaccines development to hinder the progress of this outbreak. Moreover, the questions that need to be answered are how to improve the effectiveness and efficacy of vaccines with reduced side e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 57 publications
(131 reference statements)
1
5
0
Order By: Relevance
“…In this study, we used lentiviral pseudoviruses of SARS‐CoV‐2 WT and 5 other VOCs including Alpha, Beta, Gamma, Delta, and Omicron to quantitate neutralizing antibodies in the plasma samples of mRNA‐1273, BNT162b2, and Ad26.COV2.S immunized subjects. Our results showed that all three vaccines elicited neutralizing antibodies against SARS‐CoV‐2 WT and most of the VOCs tested after full immunization, which are consistent with the success of these vaccines in controlling COVID‐19 during the early phase of the pandemic 48 . However, the efficacies of these vaccines against Delta and Omicron VOCs have been challenged.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…In this study, we used lentiviral pseudoviruses of SARS‐CoV‐2 WT and 5 other VOCs including Alpha, Beta, Gamma, Delta, and Omicron to quantitate neutralizing antibodies in the plasma samples of mRNA‐1273, BNT162b2, and Ad26.COV2.S immunized subjects. Our results showed that all three vaccines elicited neutralizing antibodies against SARS‐CoV‐2 WT and most of the VOCs tested after full immunization, which are consistent with the success of these vaccines in controlling COVID‐19 during the early phase of the pandemic 48 . However, the efficacies of these vaccines against Delta and Omicron VOCs have been challenged.…”
Section: Discussionsupporting
confidence: 81%
“…showed that all three vaccines elicited neutralizing antibodies against SARS-CoV-2 WT and most of the VOCs tested after full immunization, which are consistent with the success of these vaccines in controlling COVID-19 during the early phase of the pandemic. 48 However, the efficacies of these vaccines against Delta and Omicron…”
Section: Discussionmentioning
confidence: 99%
“…Given the observed mortality, recommendations for vaccination in the elderly (>80 years of age) should be reconsidered. In patients with multimorbidity in a suboptimal situation before vaccination, vaccine‐drug and vaccine‐disease interactions in polypharmacy users might have contributed to worsened health outcomes ( Qamar et al, 2022 ). The general vaccination response and potential immune stimulation might be sufficient to trigger decompensation of underlying diseases and prompt death ( Thomas et al, 2021 ).…”
Section: Other Cardiovascular Complications Associated With Covid-19 ...mentioning
confidence: 99%
“…After a short while, several different types of vaccines have emerged to control the pandemic [1] . Although recent studies have shown acceptable efficacy, safety and tolerability of several COVID-19 vaccines, various adverse events have been reported after vaccination [2] .…”
Section: Introductionmentioning
confidence: 99%